The role of CHA2DS2-VASc score in evaluating patients with atrial fibrillation undergoing percutaneous coronary intervention - Parfrey, S.; Teh, A.W.; Roberts, L.; Brennan, A.; Clark, D.; Duffy, S.J.; Ajani, A.E.; Reid, Christopher; Freeman, M. (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Objective The aim of the review was to assess whether CHA2DS2-VASc score is predictive of mortality in patients with atrial fibrillation undergoing percutaneous coronary intervention (PCI). Background The CHA2DS2-VASc score is validated in predicting stroke risk in atrial fibrillation. The optimum management strategy for these patients undergoing PCI is still debated. Methods The CHA2DS2-VASc score was calculated in consecutive patients with atrial fibrillation undergoing PCI in a large Australian registry between 2007 and 2013. Patients were divided into low (1-2), intermediate (3-4) and high (≥5) groups. Clinical and procedural data, 30-day, 1-year and long-Term outcomes were compared between the groups. Results A total of 564 patients were included in our analysis. Patients with high CHA2DS2-VASc scores had higher mortality rates at 1-year (2, 8, 15; P = 0.002) and long-Term (6, 20, 37; P < 0.001). High-risk patients were more likely to have renal impairment and multivessel disease. Increasing CHA2DS2-VASc score was associated with increased risk of stroke (0, 2, 6; P = 0.03). However, only 41.9% received anticoagulation, with no difference across the risk groups. When compared to low-risk, intermediate [HR 3.57; 95% confidence interval (CI), 1.28-9.92; P = 0.015] and high (hazard ratio 7.82; 95% CI, 2.88-21.24; P < 0.001) CHA2DS2-VASc scores were significant predictors of long-Term mortality. Conclusions: Higher CHA2DS2-VASc scores in patients with atrial fibrillation undergoing PCI are associated with significantly worse outcomes. Despite being high-risk, the patients in this cohort are likely undertreated with anticoagulation. Close clinical follow-up with greater utilization of anticoagulation and optimal medical therapy has the potential to improve long-Term outcomes.